Accuracy of Mesiodistal Crown Measurements using CBCT Images: A Comparison with Plaster Models - Kanak Priya1, Poonam Agrawal2 , Dinesh Kumar Bagga3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: Comparison of the mesiodistal crown measurements made on plaster models and CBCT-images.Materials & Methods: Thirty pre-existing CBCT records of the maxillary arch and type-III stoneorthodontic models, soaped and polished were used in this study. A digital vernier caliper was used to makemeasurements on each cast. The largest mesiodistal crown dimension of each tooth was measured fromcentral incisor to the second premolar of one quadrant of the maxillary arch. The OnDemand 3D program(Cybermed Co, Seoul, Korea) was used to convert CT DICOM images into 3D reconstructed images. Themesiodistal crown width measured using the OnDemand 3D program.Results: The precision of the measurements on the plaster models and on the CBCT 3D reconstructedimages were the same. There was no significant difference between them as evaluated by paired t test.Conclusion: The distance and the precision of the measurements on the plaster models and on the CBCT3D reconstructed images are equivalent. CBCT 3D reconstructed images can replace the process of makingplaster models.